2018
DOI: 10.1016/j.cub.2018.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Rab GTPases and Membrane Trafficking in Neurodegeneration

Abstract: Defects in membrane trafficking are hallmarks of neurodegeneration. Rab GTPases are key regulators of membrane trafficking. Alterations of Rab GTPases, or the membrane compartments they regulate, are associated with virtually all neuronal activities in health and disease. The observation that many Rab GTPases are associated with neurodegeneration has proven a challenge in the quest for cause and effect. Neurodegeneration can be a direct consequence of a defect in membrane trafficking. Alternatively, changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
205
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(211 citation statements)
references
References 180 publications
(216 reference statements)
4
205
0
2
Order By: Relevance
“…Given the present findings, however, GDE2 dysfunction could result from impaired endocytic trafficking rather than from loss-of-function mutations. Importantly, impaired trafficking is a hallmark of human neurodegenerative disease, including amyotrophic lateral sclerosis (ALS), Parkinson's and Alzheimer's disease (De Vos and Hafezparast, 2017;Kiral et al, 2018;McMillan et al, 2017;Schreij et al, 2016;Xu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Given the present findings, however, GDE2 dysfunction could result from impaired endocytic trafficking rather than from loss-of-function mutations. Importantly, impaired trafficking is a hallmark of human neurodegenerative disease, including amyotrophic lateral sclerosis (ALS), Parkinson's and Alzheimer's disease (De Vos and Hafezparast, 2017;Kiral et al, 2018;McMillan et al, 2017;Schreij et al, 2016;Xu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Microglia are also involved in myelin debris clearance in normal aging (Shobin et al, 2017) and in disease conditions, as shown in cuprizone-induced demyelination models (Poliani et al, 2015;Skripuletz et al, 2010). The importance of myelin debris clearance by microglia was demonstrated by blocking microglia-specific phagocytosis through inhibition of Rab7 (a key regulator in endolysosomal trafficking (Kiral, Kohrs, Jin, & Hiesinger, 2018)). This manipulation resulted in enhanced accumulation of myelin fragments in microglial endosomes and prevented remyelination (Safaiyan et al, 2016), emphasizing the microglia's key role in synaptic plasticity.…”
Section: Roles Of Microglia and Myelination In Synaptic Plasticitymentioning
confidence: 99%
“…Here, we use a Drosophila model to address the link from LRRK2 Rabs are a plausible LRRK2 substrate leading to neurodegeneration, as they act as molecular switches interacting with a range of proteins (GEFs, GAPs and GDIs) regulating supply and delivery of cargo to membranes. Indeed many of the 66 Rabs in humans have been linked to neurodegenerative disorders (9). Mutations in Rabs 29 and 39 cause Parkinson's (10)(11)(12).…”
Section: Significance Statementmentioning
confidence: 99%